No ordinary man [videorecording (DVD)] - Chin-Yee, Aisling, 1982-; Mac, Amos; Tipton, Billy, Jr (Oscilloscope Laboratories, 2022)
An in-depth look at the life of musician and trans culture icon Billy Tipton. Complicated, beautiful and historically unrivaled, this groundbreaking film shows what is possible when a community collaborates to honor the legacy of an unlikely hero.